Human Umbilical Cord Mesenchymal Stem Cells: A New Therapeutic Option for Tooth Regeneration. (2nd June 2015) - Chen, Yuanwei; Yu, Yongchun; Chen, Lin; Ye, Lanfeng; Cui, Junhui; Sun, Quan; Li, Kaide; Li, Zhiyong; Liu, Lei
Abstract : Tooth regeneration is considered to be an optimistic approach to replace current treatments for tooth loss. It is important to determine the most suitable seed cells for tooth regeneration. Recently, human umbilical cord mesenchymal stem cells (hUCMSCs) have been regarded as a promising candidate for tissue regeneration. However, it has not been reported whether hUCMSCs can be employed in tooth regeneration. Here, we report that hUCMSCs can be induced into odontoblast-like cells in vitro and in vivo . Induced hUCMSCs expressed dentin-related proteins including dentin sialoprotein (DSP) and dentin matrix protein-1 (DMP-1), and their gene expression levels were similar to those in native pulp tissue cells. Moreover, DSP- and DMP-1-positive calcifications were observed after implantation of hUCMSCs in vivo . These findings reveal that hUCMSCs have an odontogenic differentiation potency to differentiate to odontoblast-like cells with characteristic deposition of dentin-like matrix in vivo . This study clearly demonstrates hUCMSCs as an alternative therapeutic cell source for tooth regeneration.